Where do I start? : a school library handbook - Santa Clara County (Calif.). Office of Education (Worthington, Ohio : Linworth Pub., 2001)
Provides an overview and reference on library related topics for school library staff members, covering the mission of the school library, staffing, policies, organization, safety considerations, the library environment, marketing and public relations, collection development, and programming.
Includes bibliographical references and index.
Book Report.
School Library Journal.
Wilson's Children.
Professional
Keywords: Instructional materials centers -- United States -- Administration -- Handbooks, manuals, etc; School libraries -- United States -- Administration -- Handbooks, manuals, etc; Instructional materials centers -- United States -- Administration -- Handbooks, manuals, etc; School libraries -- United States -- Administration -- Handbooks, manuals, etc